Assessment of laser induction of Bruch's membrane disruption in monkey by spectral-domain optical coherence tomography. Issue 1 (21st October 2014) - Wang, Qilin; Lin, Xingyan; Xiang, Wu; Xiao, Wei; He, Mingguang
Abstract : Purpose: Laser-induced choroidal neovascularisation is a widely used model for age-related macular degeneration. The success rates of induction have been relatively low in large animals such as monkeys. Our study aimed to investigate the laser-induced damages to the Bruch's membrane of monkeys using the spectral-domain optical coherence tomography (OCT). Methods: Laser photocoagulation was performed in the posterior and peripheral fundus of a rhesus monkey using a 532 nm laser. The lesions were examined by fundus photography and spectral-domain OCT immediately after the procedure. Fluorescein angiography was performed after 3 and 4 weeks in the animal to assess the development of choroidal neovascularisation. Results: A total of 44 lesions were produced in both eyes of the animal. Subretinal bubbles with or without haemorrhage were observed at 41 spots during the procedure. Spectral-domain OCT showed that laser damages varied considerably among lesions and the disruption of the Bruch's membrane could be visualised at 23 spots on the OCT images. Leakage of fluorescein was only observed after 3 and 4 weeks within the macular area at lesions where Bruch's membrane disruptions had been detected by OCT. Conclusions: The presence of subretinal bubbles with haemorrhage is not an accurate indicator for successful disruption of the Bruch's membrane. Instead, spectral-domain OCT provides a better alternative to assess the retinal damages to the Bruch's membrane during laser induction of choroidal neovascularisation in monkeys.